Synthesis of 99m TcN-clinafloxacin dithiocarbamate complex and comparative radiobiological evaluation in Staphylococcus aureus infected mice - Syed Shah; Mohammad Khan (World Journal of Nuclear Medicine)
Clinafloxacin dithiocarbamate (CNND) preparation and radiolabeling through [ 99m Tc ≡ N] 2+ core with the gamma (g) emitter ( 99m Tc) was assessed. The potentiality of the 99m Tc V ≡ N-CNND complex was investigated as perspective a Staphylococcus aureus (S.a.) in vivo infection radiotracer in terms of radiochemical stability in normal saline (n.s.), human serum (h.s.), binding efficacy with live and heat killed S.a. and biodistribution in female nude mice model (FNMD). More than 90% stability was observed in n.s. for 4 h with the highest yield of 98.70 ± 0.26% at 30 min after reconstitution. In h.s., the 99m Tc V ≡ N-CNND complex was found stable up to 16 h with 15.35% side products. Maximum in vitro binding (68.75 ± 0.80%, 90 min) with S.a. was observed after 90 min of incubation. In FNMD, (infected with live strain) approximately six-fold higher uptakes was noted in the infected to inflamed and normal muscles. The higher stability in n.s., h.s., higher S.a. (live) up take with specific and targeted in vivo distribution confirmed potentiality of the 99m Tc V ≡ N-CNND complex as perspective S.a. in vivo infection radiotracer.